Activation and identification of five clusters for secondary metabolites in Streptomyces albus J1074. Issue 3 (4th March 2014) - Olano, Carlos; García, Ignacio; González, Aranzazu; Rodriguez, Miriam; Rozas, Daniel; Rubio, Julio; Sánchez‐Hidalgo, Marina; Braña, Alfredo F.; Méndez, Carmen; Salas, José A.
Summary S treptomyces albus J1074 is a streptomycete strain widely used as a host for expression of secondary metabolite gene clusters. Bioinformatic analysis of the genome of this organism predicts the presence of 27 gene clusters for secondary metabolites. We have used three different strategies for the activation of some of these silent/cryptic gene clusters in S. albus J1074: two hybrid polyketide‐non‐ribosomal peptides (PK‐NRP) (antimycin and 6‐epi‐alteramides), a type I PK (candicidin), a non‐ribosomal peptides (NRP) (indigoidine) and glycosylated compounds (paulomycins). By insertion of a strong and constitutive promoter in front of selected genes of two clusters, production of the blue pigment indigoidine and of two novel members of the polycyclic tetramate macrolactam family (6‐epi‐alteramides A and B) was activated. Overexpression of positive regulatory genes from the same organism also activated the biosynthesis of 6‐epi‐alteramides and heterologous expression of the regulatory gene pimM of the pimaricin cluster activated the simultaneous production of candicidins and antimycins, suggesting some kind of cross‐regulation between both clusters. A cluster for glycosylated compounds (paulomycins) was also identified by comparison of the high‐performance liquid chromatography profiles of the wild‐type strain with that of a mutant in which two key enzymes of the cluster were simultaneously deleted.